Pre and post natal drivers of childhood intelligence: Evidence from Singapore - Gail Pacheco; Mary Hedges; Chris Schilling; Susan Morton (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2011)
In this study, we seek to investigate what influences children's intelligence in early childhood. The Singapore Cohort Study of the Risk Factors of Myopia (SCORM) is used in to assess determinants of childhood IQ and changes in IQ. This longitudinal data set, collected from 1999, includes a wealth of demographic, socioeconomic, and prenatal characteristics. The richness of the data allows us to employ various econometric approaches including the use of ordered and multinomial logit analysis. We find mother's education to be a consistent and key determinant of childhood IQ. We also find that father's education and school quality are key drivers for increasing IQ levels above the average sample movement.
Keywords: 330; Childhood IQ; Prenatal characteristics; Socioeconomic determinants; Longitudinal study